2013
DOI: 10.1007/s13311-013-0208-3
|View full text |Cite
|
Sign up to set email alerts
|

Development of Inducible Leucine-rich Repeat Kinase 2 (LRRK2) Cell Lines for Therapeutics Development in Parkinson's Disease

Abstract: The pathogenic mechanism(s) contributing to loss of dopamine neurons in Parkinson's disease (PD) remain obscure. Leucine-rich repeat kinase 2 (LRRK2) mutations are linked, as a causative gene, to PD. LRRK2 mutations are estimated to account for 10 % of familial and between 1 % and 3 % of sporadic PD. LRRK2 proximate single nucleotide polymorphisms have also been significantly associated with idiopathic/sporadic PD by genome-wide association studies. LRRK2 is a multidomain-containing protein and belongs to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 66 publications
(107 reference statements)
0
4
0
Order By: Relevance
“…Recognizing that LOF variants in LRRK2 are not damaging to an individual indicates that kinase inhibitors and allele-specific oligos could be used as PD therapies. Previous studies 14,15 have shown that mutant alleles of LRRK2 can be selectively knocked down in various cell lines using allele-specific oligos. Additional studies of chronic LRRK2 kinase inhibition in mice and nonhuman primates 16,17 have shown that multiple inhibitors are effective at reducing LRRK2 phosphorylation in the brain with no adverse effects in the kidneys; however, a lysosomal phenotype has been reported in treated nonhuman primate lungs that is similar to reports from Lrrk2 knockout mice.…”
Section: Discussionmentioning
confidence: 99%
“…Recognizing that LOF variants in LRRK2 are not damaging to an individual indicates that kinase inhibitors and allele-specific oligos could be used as PD therapies. Previous studies 14,15 have shown that mutant alleles of LRRK2 can be selectively knocked down in various cell lines using allele-specific oligos. Additional studies of chronic LRRK2 kinase inhibition in mice and nonhuman primates 16,17 have shown that multiple inhibitors are effective at reducing LRRK2 phosphorylation in the brain with no adverse effects in the kidneys; however, a lysosomal phenotype has been reported in treated nonhuman primate lungs that is similar to reports from Lrrk2 knockout mice.…”
Section: Discussionmentioning
confidence: 99%
“…Experiment conducted in LRRK2 p.G2019S cells with a doxorubicin inducible neuritic phenotype showing a reversed phenotype after adding a specific and potent kinase inhibitor, IN-1. Moreover, LRRK2 p.G2019S-mediated blunting of neurite extension is reversed by Lentivirus-mediated transfer of LRRK2 p.G2019S allele-specific small hairpin RNA [ 119 ]. Another similar study conducted in transgenic C. elegans which expressing human p.R1441C- and p.G2019S-LRRK2 showed that TTT-3002 and LRRK2-IN1 rescued the behavioral deficit characteristic of dopaminergic impairment.…”
Section: Lrrk2 As a Therapeutic Target For Parkinsonismmentioning
confidence: 99%
“…Mutations in the KIN and ROCO domains alter constitutive phosphorylation of LRRK2 and are associated with PD pathogenesis [102]. The G2019S mutation of LRRK2 increased phosphorylation in dopaminergic cell lines, resulting in abnormal neurite growth and increased neuronal vulnerability [103]. Mutation in G2019S also increased LRRK2 kinase activity [104, 105], while inhibition of kinase activity reduced its constitutive phosphorylation [103].…”
Section: Lrrk2mentioning
confidence: 99%
“…The G2019S mutation of LRRK2 increased phosphorylation in dopaminergic cell lines, resulting in abnormal neurite growth and increased neuronal vulnerability [103]. Mutation in G2019S also increased LRRK2 kinase activity [104, 105], while inhibition of kinase activity reduced its constitutive phosphorylation [103]. This indicates that G2019 mutations increase LRRK2 constitutive phosphorylation and promote LRRK2 kinase activity.…”
Section: Lrrk2mentioning
confidence: 99%